2021
DOI: 10.31124/advance.16644889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptance and adherence to COVID-19 preventive measures are shaped predominantly by conspiracy beliefs, mistrust in science and fear - A comparison of more than 20 psychological variables

Abstract: This pre-print-version reports the results of survey-data (n = 374). Information regarding methodology can be found in the document. Abstract:

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Thus, it is expected that anxiety results in high adherence to preventive measures, although research evidence remains mixed. Whilst some studies have shown positive relationship between anxiety and adherence to preventive measure, others found no or negative association [97,98]. The findings of this study thus concur with others that found that increased anxiety is associated with positive preventive behaviour.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it is expected that anxiety results in high adherence to preventive measures, although research evidence remains mixed. Whilst some studies have shown positive relationship between anxiety and adherence to preventive measure, others found no or negative association [97,98]. The findings of this study thus concur with others that found that increased anxiety is associated with positive preventive behaviour.…”
Section: Discussionsupporting
confidence: 87%
“…Related studies find that personality does not predict views on alternative medicine (Furnham, 2007), while need for cognition is positively related to science attitudes (Feist, 2012;Kudrna et al, 2015;Mather, 2009), sensation-seeking positively predicts propensity to talk about science (Hwang & Southwell, 2007), and empathy matters for perceptions of science-society relations and support for ethically questionable research (Jach & Buczek, 2021;Ruisch et al, 2021). Additionally, multiple studies find that academic performance relates to personality (Chamorro-Premuzic & Furnham, 2003;Eyong et al, 2014;Hakimi et al, 2011;Hong & Lin, 2011), two studies indicate that personality predicts belief in "pseudoscience" such as astrology (Andersson et al, 2022;García-Arch et al, 2022), and a recent study finds that covid-related behavior is predicted by personality traits (Hartmann & Müller, 2022).…”
Section: Does Personality Predict Science Attitudes?mentioning
confidence: 99%
“…Conspiracy beliefs are assumptions of secret plots by powerful evil groups who cover up information to suit their own interests (Douglas et al, 2017). Recent studies suggest that such beliefs undermine preventive behaviour, and are therefore a barrier in preventing the spread of SARS-CoV-2 (e.g., Hartmann & Müller, 2022; Pummerer et al, 2022). Given this relevance, the scientific interest in understanding the psychology of conspiracy beliefs has been exploded during the last 2 years.…”
mentioning
confidence: 99%
“…Participants were informed that there was an object hidden in some but not all of the stimuli, and for each stimulus they rated whether they perceived that there was an object (1 = definitively no object, 6 = definitively an object). Paranormal belief was measured by the Proneness to the Paranormal Scale (12 items), and COVID-19 conspiracy beliefs by five self-created items, such as ‘COVID-19 could have been stopped right at the start, but the large companies made a business out of keeping it going’ (see Hartmann & Müller, 2022 for full details of these measurements).…”
mentioning
confidence: 99%